A kick in the attitude : an energizing approach to recharge your team, work, and life - Glenn, Sam, 1971- (Wiley, 2010)
"If your thoughts and focus are not right or not working in your favor, you need to shock your system to break the pattern or current track you are on in order to get out of the habit of thinking negatively and onto a track that benefits your life"--Page 6.